New era in plant alternative splicing analysis enabled by advances in high-throughput sequencing (HTS) technologies - Bedre, Renesh (2019)
Alternative splicing (AS) is a crucial posttranscriptional mechanism of gene expression which promotes transcriptome and proteome diversity. At the molecular level, splicing and AS involves recognition and elimination of intronic regions of a precursor messenger RNA (pre-mRNA) and joining of exonic regions to generate the mature mRNA. AS generates more than one mRNA transcript (transcripts) differing in coding and/or untranslated regions (UTRs). AS can be classified into four major types including the exon skipping (ES), intron retention (IR), alternative donor (AD), and alternative acceptor (AA), of which IR is the most prevalent event in plants (Mandadi and Scholthof, 2015). In addition to these AS types, a subfamily of IR called exitrons, which has dual features of introns and protein-coding exons were first reported in Arabidopsis thaliana (Arabidopsis) and later also found in humans (Marquez et al., 2015). These spliced transcripts influence multiple biological processes such as growth, development and response to biotic and abiotic stresses in plants (Filichkin et al., 2015; Mandadi and Scholthof, 2015; Wang et al., 2018a).